Perpecahan Kerajaan Israel Utara Dan Selatan Dalam Analisis Diakronik - Semuel Simbolon; Herman Simarmata (Peneliti.net, 2023)
In this life it is inseparable from the problems that come and go, by facing problems a person can learn to be a mature person and be able to solve them. Sometimes with problems, something can create a gap between one another. That is what happened to the nation of Israel, having problems with God and not solving it will make people fall into sin. There will be other problems when someone does not ask God for forgiveness, like Solomon, who did not obey the word of God that came to him, but instead grew away from God. Which resulted in the division of Rehoboam's descendants, where Jeroboam, at God's will, rebelled against King Rehoboam. This paper aims to determine the diacronic analysis of the split between the kingdom of North Israel and South Israel. The method used in this writing is descriptive qualitative through libraries using books and online journals. Therefore the research results in this diachronic analysis are that the cause of the split between the kingdom of North Israel and southern Israel is due to Solomon's rebellion against the God of Israel, the rebellion of the people of northern Israel to King Rehoboam and because of God's punishment and God's will which caused the kingdom of Israel to split into two kingdoms